The Influence of Corporate Governance Characteristics on Cash Holding - Eka Putri NF Harahap; Erna Widiastuty (Journal of Applied Accounting and Taxation, 2024)
This study aims to provide empirical evidence of the influence of corporate governance characteristics on cash holding. The population in this study is all public companies listed on the New York Stock Exchange (NYSE) for the 2020-2022 period. Sample selection was carried out using the purposive sampling method. Based on the sampling, observations were obtained as many as 568 companies-year. In this study, cash ownership is a dependent variable measured by cash and cash equivalents to total assets. Meanwhile, the independent variables of governance characteristics in this study consist of gender diversity measured by the number of female boards in the company, the size of the Board measured by the number of boards in the company, and board meetings measured by the number of meetings conducted by the board. The results of the study found empirical evidence that gender diversity has a positive and significant effect on cash holding. Meanwhile, the size of the Board and the Board meeting have no effect on cash holding. The implication of the results of this study is that the diversity of the Board mitigates managers' decisions in cash management.